Exploring Student Mental Models and Student Experiences to Improve the Teaching Practice of Cell and Molecular Biology (American Journal of Multidisciplinary Research and Innovation, 2022)
Teaching and Learning Biology requires a lot of memorizations of concepts, principles, and laws which may be one of the reasons why students find this area of knowledge highly conceptual. This action research is conducted to improve the teaching practice of Cell and Molecular Biology by investigating and exploring the mental models of students in learning this course under the program, Bachelor of Secondary Education (BSED) Major in Science. This study utilized an action research design by developing learning modules that contain asynchronous tasks which allowed students to design their own concept maps and other visual organizers to explain highly technical concepts in Cell and Molecular Biology. This targets to improve students’ critical thinking and enhance comprehension of difficult concepts which were assessed through summative assessments. Based on the results of this study, the students frequently used concept maps and bubble topical organizers or clusters of objects that show linkages among the topics that were discussed in the modules. Students relatively agreed that use of concept mapping helped them organize their ideas in the entire course of cell and molecular biology. This study recommends the testing of this intervention to other disciplines in science education such as in genetics & biotechnology and in anatomy and physiology to establish the consistency of results.